Analysis of Cooling System Abnormalities in Diesel Generators at MV. Meratus Kahayan - Mangengke, Jeremy Suryadharma; Marsudi, Sugeng (Universitas Hang Tuah, 2024)
The cooling system in a diesel generator is designed to maintain the engine temperature under ideal conditions during prolonged operation. If the cooling system experiences any abnormalities, it can negatively affect the performance of the diesel generator, resulting in suboptimal operation. However, these abnormalities can be addressed by understanding the system, identifying the causal factors, understanding the resulting impacts, and implementing appropriate solutions. This research utilizes a qualitative research method and employs fishbone analysis for data analysis. The findings will be presented descriptively to explain and provide detailed information based on the facts obtained during the research conducted on the ship. The conclusion of the study reveals that the abnormality in the diesel generator cooling system is primarily caused by inadequate flow of seawater as a cooling medium due to blockages in the sea chest filter and the fresh water cooler tube of the diesel generator. Moreover, the lack of coordination between the engine crew and the deck crew also contributes to these issues. As a result, the temperature of the coolant and the diesel generator oil increases. To address these issues, maintenance activities need to be performed on all components of the diesel generator cooling system according to the Planned Maintenance System (PMS).